Ameliorative Impact of Tecoma stans on Streptozotocin-Induced Diabetic Cardiomyopathy in Wistar Rats - S. Kameshwaran; M. Ravisankar; P. Srinivasan; V. Suresh (Advanced Concepts in Pharmaceutical Research Vol. 1, 2023)
The objective of this study was to see how an ethanolic extract of Tecoma stans affected diabetic cardiomyopathy in wistar rats after streptozotocin-induced diabetes. The pathogenesis of diabetic cardiomyopathy (DCM) is complex, and the therapeutic options available to treat DCM are limited. A single intravenous dosage of (Streptozotocin 45 mg/kg) produced diabetes in male wistar rats. Blood pressure, serum lactate dehydrogenase (LDH), glucose apolipoprotein B, and lipids were measured, as well as heart weight, caspase-3, sodium potassium adenosine triphosphatase (Na + -K + ATPase), and DNA laddering. The obtained result showed that the administration of ethanolic extract of Tecoma stans (120 mg/kg/p.o.) significantly (P < 0.01) reduced myocyte loss by suppressing the levels of cardiac caspase-3, DNA laddering; mean arterial blood pressure and heart rate as well as serum LDH, glucose, apolipoprotein B and lipids levels. Further, it augmented the heart weight and cardiac Na+ K + ATPase activity in diabetic rats. Finally, an ethanol extract of Tecoma stans was found to have considerable anti-apoptotic potential in Streptozotocin-induced diabetic cardiomyopathy.